Hubungan Open Access Institutional Repository (OAIR) dengan Produktivitas Ilmiah pada Dosen di Perguruan Tinggi - Bulqis Khumairo; Dian Novita Fitriani (Media Pustakawan, 2019)
OA becomes a new model in the scientific communication process. In various studies show that OA gives the impact of increasing research by giving free access to articles for all who are interested. The OA movement is not only limited to the process of disseminating and promoting work from the research community, but has evolved into individual institutional repositories, electronic archives of research results of staff working on these institutions. Some academic libraries have begun to develop Open Access Institutional Repositories (OAIR). Along with the development of OAIR, the academic community is demanded to be productive in conducting scientific publications. The development of OAIR and scientific publications are very important components in scientific communication. This study aims to determine whether there is a relationship between the availability and accessibility of OAIR with the scientific productivity of lecturers. The method used in this research is descriptive quantitative. The number of respondents was 70 lecturers from 3 universities who presented the 2018 SINTA Awards, namely the University of Indonesia, UIN Sunan Gunung Djati and the Ministry of Health II Jakarta Poltekkes. Data collection is done by using questionnaires in the form of online and offline. The results of this study indicate that the availability and accessibility of the OAIR system has a multiple correlation coefficient of 0.812 and a significance value of 0,000, so there is a positive influence and has a very strong relationship on scientific productivity among lecturers.